PURA syndrome—a genetic cause of a neurodevelopmental disorder—case report - Kobak, Jacek; Szczupak, Mateusz; Czerkiewicz, Karolina; Bielocerkowski, Sergiusz; Krupa-Nurcek, Sabina (Frontiers in Pediatrics, 2025)
IntroductionPURA syndrome is a rare genetic disorder first described in the medical literature in 2014. It is caused by pathogenic variants in the PURA gene, which is located on chromosome 5. The PURA gene is crucial for the production of the pur-α protein, which is expressed in all tissues, including the nervous system, muscles, and blood. The pur-α protein plays a vital role in normal brain development. The estimated incidence of PURA syndrome is 1 in 1,000,000, and as of 2024, approximately 706 cases of the syndrome have been identified worldwide.Aim of studyThe aim of the study was to present a case description of PURA syndrome and the genetic basis of the neurodevelopmental disorder in a 15-year-old girl.Case reportThis manuscript presents the case of a 15-year-old girl of Polish descent diagnosed with PURA syndrome through genetic testing. She was admitted to the Department of Orthopedics and Spine Surgery at the Medical University of Gdansk for surgical treatment of advanced idiopathic scoliosis caused by a postural defect.ConclusionPURA syndrome is a rare genetic condition that requires further research and observation. Although it shares many clinical features with other neurological disorders, certain symptoms—such as speech disorders, the ability to follow and execute simple commands, and an excessive acoustic reaction to surprises—should raise suspicion of this condition. These indicators should prompt genetic testing for confirmation and the implementation of appropriate multidisciplinary care for the patient.